Cyclin-dependent kinase 1 targeting improves sensitivity to radiation in BRAF V600E colorectal carcinoma cells - Girolamo Spagnoletti; Valeria Li Bergolis; Annamaria Piscazzi; Francesca Giannelli; Valentina Condelli; Lorenza Sisinni; Giuseppe Bove; Giovanni Storto; Matteo Landriscina (Tumor Biology)
Objectives: Preoperative chemoradiation is currently the standard of care in locally advanced rectal carcinoma, even though a subset of rectal tumors does not achieve major clinically meaningful responses upon neoadjuvant chemoradiation. At present, no molecular biomarkers are available to predict response to neoadjuvant chemoradiation and select resistant tumors willing more intense therapeutic strategies. Thus, BRAF mutational status was investigated for its role in favoring resistance to radiation in colorectal carcinoma cell lines and cyclin-dependent kinase 1 as a target to improve radiosensitivity in BRAF V600E colorectal tumor cells. Methods: Colony-forming assay and apoptotic rates were evaluated to compare the sensitivity of different colon carcinoma cell lines to ionizing radiation and their radiosensitivity upon exposure to BRAF and/or cyclin-dependent kinase 1 inhibitory/silencing strategies. Cyclin-dependent kinase 1 expression/subcellular distribution was studied by immunoblot analysis. Results: Colon carcinoma BRAF V600E HT29 cells exhibited poor response to radiation compared to BRAF wild-type COLO320 and HCT116 cells. Interestingly, neither radiosensitizing doses of 5-fluoruracil nor BRAF inhibition/silencing significantly improved radiosensitivity in HT29 cells. Of note, poor response to radiation correlated with upregulation/relocation of cyclin-dependent kinase 1 in mitochondria. Consistently, cyclin-dependent kinase 1 inhibition/silencing as well as its targeting, through inhibition of HSP90 quality control pathway, significantly inhibited the clonogenic ability and increased apoptotic rates in HT29 cells upon exposure to radiation. Conclusion: These data suggest that BRAF V600E colorectal carcinoma cells are poorly responsive to radiation, and cyclin-dependent kinase 1 represents a target to improve radiosensitivity in BRAF V600E colorectal tumor cells.